Financial analysis of dipping strategies for indigenous cattle under ranch conditions in Uganda - Okello-Onen, Joseph; Mukhebi, A.W.; Tukahirwa, E.M.; Musisi, G.; Bode, E.; Heinonen, R.; Perry, Brian D.; Opuda-Asibo, J. (Elsevier, 1998)
A financial analysis was performed to assess the performance of three acaricide-treatment groups of indigenous breeds (Zebu and Nganda) of cattle on a ranch in Luwero District, Uganda. The treatments were based on different frequencies: twice-a-week dipping, once-a-month dipping and no tick control. The objective was to evaluate the economic justification for intensive acaricide application for tick and tick-borne disease control in Uganda. Data were collected by monitoring cattle performance over a period of 34 months. Biological data collected included the number of cows at the beginning and end of the study, net starting liveweight, number of calves born, number of animals dying due to tick-borne diseases and other causes, number of animals sold or slaughtered and milk yield. Records of variable costs (acaricides, drugs, labour, etc.) and output prices were assembled and calculated by treatment group. Gross margin and marginal analysis were used in the financial analysis. The exchange rate in 1990-1993 was one US$ to 1200 Uganda shillings. The gross benefits obtained from animal sales, herd value and milk yield were Uganda shillings 1175, 1389 and 1311 per kg of net starting liveweight for animals dipped twice-a-week, once-a-month and not dipped, respectively. The variable costs were Ug. shs. 424, 390 and 360 per kg of net starting liveweight, respectively. Consequently, the gross margins were Ug. shs. 751, 999 and 951 per kg of net starting liveweight. Furthermore, the marginal rate of return (MRR) in changing from no tick control to once-a-month dipping was 160%, while changing from no tick control to twice-a-week dipping was negative (-313%). The above results showed that the value of increased gains in production obtained from twice-a-week dipping strategy does not offset the costs of inputs for intensive dipping. Once-a-month dipping (strategic) therefore appears to be the most-profitable tick-control strategy for the farmer. The need to conduct further studies in different livestock- production systems and to rationalise future tick control policies is discussed.